Performance Analysis of SISO and MIMO FSO Communication Systems Over Turbulent Channels - Peppas, Kostas; Nistazakis, Hector E.; Assimakopoulos, Vasiliki D.; Tombras, George S. (IntechOpen, 2012)
None